Acupuncture in chemotherapy-induced dysgeusia (AcuDysg): study protocol of a randomised controlled trial. Issue 3 (10th March 2023) - Huber, Christine; Zhang, Linxin; Schlaeppi, Marc; Müller, Twyla; Roll, Stephanie; Voiss, Petra; Barth, Jürgen; Driessen, Christoph; Witt, Claudia M
Abstract : Introduction: Dysgeusia is a common side effect of chemotherapy in patients with cancer, but to date, there is no effective treatment. Many patients with cancer request complementary medicine treatment in addition to their cancer treatments, and acupuncture is highly accepted for patients with cancer; however, evidence regarding the effectiveness of acupuncture for dysgeusia is scarce. The study investigates the effectiveness of an additional dysgeusia-specific acupuncture plus self-acupressure intervention compared with supportive acupuncture plus self-acupressure intervention alone for chemotherapy-induced dysgeusia in patients with cancer. Methods and analysis: This is a multicentre, randomised, controlled and two-armed parallel-group, single-blind trial involving 130 patients. Both groups will receive eight sessions of acupuncture treatment over a period of 8 weeks and will be trained to perform self-acupressure (eLearning combined with therapist instruction) at predefined acupressure points once a day during the whole treatment period. Patients in the control group will receive supportive routine care acupuncture and self-acupressure treatment only; in addition to this treatment, the intervention group will receive the dysgeusia-specific acupuncture and acupressure within the same treatment session. The primary outcome is the perceived dysgeusia over 8 weeks, measured weekly after the acupuncture treatment. Secondary outcomes include the indices from the objective taste and smell test, weight loss, perceived dysgeusia, fatigue, distress, nausea and vomiting, odynophagia, xerostomia and polyneuropathy, as well as quality of life at the different time points. Ethics and dissemination: The study has been approved by the Cantonal Ethics Committee (CEC) (Kanton Zürich Kantonale Ethikkommission) (approval no. KEK-ZH-Nr. 2020–01900). The results will be submitted to a peer-reviewed journal for publication. Trial registration numbers: DRKS00023348, SNCTP000004128.